Prodrugs of phosphonates and phosphates: crossing the membrane barrier - Wiemer, Andrew J. (Top Curr Chem, 2015)
A substantial portion of metabolism involves transformation of phosphate esters, including pathways leading to nucleotides and oligonucleotides, carbohydrates, isoprenoids and steroids, and phosphorylated proteins. Because the natural substrates bear one or more negative charges, drugs that target these enzymes generally must be charged as well but small charged molecules can have difficulty traversing the cell membrane other than by endocytosis. The resulting dichotomy has stimulated abundant effort to develop effective prodrugs, compounds that carry little or no charge to enable them to transit biological membranes but then able to release the parent drug once inside the target cell. This chapter will present recent studies on advances in prodrug forms, along with representative examples of their application to marketed and developmental drugs.